O-CITRI Soap: Antibacterial Paper Soap Made from Orange Peel (Citrus sinensis L.) and Basil (Ocimum sanctum L.) - Fitriyani, Fitriyani; Bustomi, Mochammad Y. A.; Maulina, Novia; Kinasih, Larasati S.; Arriziq, Muhammad A. (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Basil (Ocimum sanctum L.) have a dominant content of citral compounds with antibacterial activity. Another plant suspected to contain antibacterial bioactive components is orange peel. Orange peel (Citrus sinensis L) contains phenolic compounds (phenolic acids, flavonones, and polymethoxylated flavones), carotenoids, and ascorbic acid. Phenolic compounds are known to have several activities such as antimicrobial, antioxidant, anticancer, anti-inflammatory, and anti- allergic. The aim of this research is to prove that the combination of orange peel and basil extracts has antibacterial effects against Staphylococcus aureus, which can be formulated as paper soap which is named O-Citri. This research method is experimental, involving the physical and chemical evaluation of the formulation, as well as antibacterial activity testing. The research results show that the combination of orange peel and basil extracts in the paper soap formulation has antibacterial effects. The highest concentration combination for antibacterial activity is F1 with a ratio of orange peel and basil extract at 5%:15%.